2021
DOI: 10.1039/d1nr03502a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced penetrative siRNA delivery by a nanodiamond drug delivery platform against hepatocellular carcinoma 3D models

Abstract: Comprehensive analysis of hepatocellular carcinoma 3D models revealed enhanced penetrative siRNA delivery by a nanodiamonds compared to liposomes. Nanodiamonds were able to improve siRNA's gene knockdown and anti-cancer effects in 3D tumor models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 111 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…Negatively charged proteins, present in FBS, have been reported to competitively bind to nanocarriers and enhance release ( Ju and Yeo, 2012 ; Wang et al, 2014 ). Xu et al (2021) , also reported that siRNA release from nanodiamonds was increased by enhancing the FBS percentage from 1.25% to 10% in the release media. In the intracellular environment, the presence of various soluble biological polyanions can competitively replace and dissociate the nucleic acids from nanocomplexes ( Cozzolino et al, 2021 ).…”
Section: Resultsmentioning
confidence: 89%
“…Negatively charged proteins, present in FBS, have been reported to competitively bind to nanocarriers and enhance release ( Ju and Yeo, 2012 ; Wang et al, 2014 ). Xu et al (2021) , also reported that siRNA release from nanodiamonds was increased by enhancing the FBS percentage from 1.25% to 10% in the release media. In the intracellular environment, the presence of various soluble biological polyanions can competitively replace and dissociate the nucleic acids from nanocomplexes ( Cozzolino et al, 2021 ).…”
Section: Resultsmentioning
confidence: 89%
“…7(a)). 168 Other studies revealed that protamine sulphate-coated ND systems facilitated not only the delivery of microRNA mimics for the treatment of esophageal cancer and triple negative breast cancer, but also the signal enhancement for in vivo tumour imaging when compared to uncoated NDs. 169,170 Our group also reported the delivery of antisense oligonucleotide (ASO) 4625 using NDs coated with TAT and NLS.…”
Section: Gene Therapymentioning
confidence: 99%
“…Thus, siRNA exerts its therapeutic effect. 141 Theranostic Applications of Carbon Nanodots. Carbon dots (CD) are carbon analogues and were first discovered in 2004 during the preparation of single-walled carbon nanotubes.…”
Section: Theranostic Applicationsmentioning
confidence: 99%
“…ND-siRNA complexes absorbed by the cell enter the cytoplasm through an endosomal escape mechanism and protect the siRNA against degradation. Thus, siRNA exerts its therapeutic effect …”
Section: Carbon-based Nanoparticles For Theranostic Applicationsmentioning
confidence: 99%